Towns between Empires: Good Governance and “Police” in Case Studies from Transylvania, Wallachia, and Moldavia, 1500s–1800s (Amsterdam University Press, 2025)
Towns between Empires contains contributions regarding urban administration and governance in the historical regions that are now in Romania, and that fall under the early modern concept of good governance. Chapters give insight into the concepts and solutions applied by urban governments to political, social and economic issues that were under their care and control. The authors approach various aspects of this topic: town councils as political and economic elites of early modern towns, urban political systems as models of early modern ideas of administration, relations between towns and central authorities (the Prince), healthcare as good governance. The chapters in the volume capture the widest possible variety of political and administrative systems in the region. Transylvanian towns were structured and governed similarly to other small Central European urban centers, however significant diversity can be discerned following the Reformation. Moldavian and Wallachian towns in the 18th and 19th century are little known to international scholarship, and the chapters in this volume will fill this gap.